The Role of Health Officer Related to Adherence to Iron Tablet Supplementation among Pregnant Women in Central Aceh in 2021 - MS, Sri Wahyuni; Barirah Madeni; Hasritawati (HM Publisher, 2022)
Background. Coverage of Fe tablets in Aceh Tengah District is very low, even lower than other districts in Aceh; namely 12.4 percent for Fe 1 and 10.56 percent for Fe3. Failure to distribute these tablets in this district may lead to an increase in the prevalence of anemia. One of the reasons is that the monitoring, recording, and reporting system by health officers in consuming Fe tablets and in routinely checking Hb levels is not good enough. This study aims to analyze the effect of the role of leadership (customers, communicators, motivators, facilitators, and counselors) on the adherence of pregnant women to consuming Fe tablets in the Central Aceh Regency in 2021. Methods. This type of research is a survey with a cross-sectional approach. The population is all pregnant women in the Aceh Tengah Regency area with a gestational age of more than 20 weeks, or it could be less than 20 weeks, provided that this is the first visit and has made a health visit at the health center. Methods of collecting data by interviewing and checking the health development of pregnant women with Editing, Coding, Entry, and Cleaning. Data were analyzed by univariate, bivariate, and multivariate. Results. The results of the multivariate analysis with logistic regression obtained the facilitator variable has the greatest influence on compliance in consuming Fe tablets with a value of OR = 14,166 meaning pregnant women who accept the role of health officers as facilitators will obediently consume Fe tablets as much as 14,166 times when compared to mothers who do not accept the role of health officers as customers. Conclusion. The low adherence to Fe tablet consumption was due to the fact that the number of Fe tablets given by health officers to pregnant women in Aceh Tengah Regency was not up to the standard, which was 90 tablets. Customers and facilitators have a relationship with the adherence of pregnant women to consuming Fe tablets. The facilitator has the greatest influence on compliance in consuming Fe tablets.